1993
DOI: 10.1002/jnr.490340104
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic and molecular properties of cultured enteric glia

Abstract: Enteric glia, the support cells of myenteric ganglia, have been widely studied with respect to their morphology and immunohistochemical phenotype, but little is known about their functional properties. We developed a method for the amplification of enteric glia from newborn guinea pigs to further characterize these cells. Treatment with a combination of basic fibroblast growth factor and the adenylate cyclase activator, cholera toxin, permitted expansion of enteric glial cultures to confluence and serial passa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…A small number of EGCs in the myenteric plexus are, however, positive, suggesting that only a subpopulation of EGCs express an astrocyte-specific GFAP isoform, although the functional significance of this observation has yet to be determined. Electrophysiological studies have also revealed heterogeneity among EGCs by demonstrating the presence of a voltage-gated tetrodotoxin-sensitive Na ϩ channel in a subpopulation of EGCs (Broussard et al, 1993;Hanani et al, 2000). The physiological significance of a voltagegated Na ϩ channel function in a small percentage of EGCs remains unclear as these cells are largely electrically inert.…”
Section: Egc Heterogeneity and Enteric Glial Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…A small number of EGCs in the myenteric plexus are, however, positive, suggesting that only a subpopulation of EGCs express an astrocyte-specific GFAP isoform, although the functional significance of this observation has yet to be determined. Electrophysiological studies have also revealed heterogeneity among EGCs by demonstrating the presence of a voltage-gated tetrodotoxin-sensitive Na ϩ channel in a subpopulation of EGCs (Broussard et al, 1993;Hanani et al, 2000). The physiological significance of a voltagegated Na ϩ channel function in a small percentage of EGCs remains unclear as these cells are largely electrically inert.…”
Section: Egc Heterogeneity and Enteric Glial Networkmentioning
confidence: 99%
“…Interestingly, EGCs share these phenotypic and functional properties with astrocytes. Indeed, EGCs express voltage-activated inward and outward potassium channels (Broussard et al, 1993;Hanani et al, 2000), and electrophysiological studies have demonstrated voltage-gated potassium currents in isolated EGCs (Broussard et al, 1993). Furthermore, passive currents have been observed among gap junction-coupled EGCs in isolated ganglia (Hanani et al, 2000).…”
Section: Neuroprotective and Neuromodulatory Functions Of Egcmentioning
confidence: 99%
“…The expression of trophic factors by enteric glia has not been described; however, it was demonstrated that exogenous bFGF can increase the electrophysiological properties of cultured enteric glia (Broussard et al, 1993). bFGF immunoreactivity in the enteric glia described in the present study suggests a paracrine trophic action of bFGF on the enteric neurons.…”
Section: Discussionmentioning
confidence: 79%
“…The role of neurotrophic factors in neuronal development and maintenance is well established, and investigations of their actions in the enteric nervous system have been carried out (Mulholland et al, 1992(Mulholland et al, , 1994Broussard et al, 1993;Kobayashi et al, 1994;Schafer et al, 1995). However, the presence of growth factors in the enteric nervous system has not been demonstrated.…”
mentioning
confidence: 98%
“…To exclude any potential contamination by glia cells, coverslips were superfused with KCl (55 mM) at the end of the experiments, and cells were excluded if intracellular Ca 2+ did not increase. 17 In this study, n equals the number of neurons examined. At least four coverslips were used for each experimental condition.…”
Section: Discussionmentioning
confidence: 99%